Efektivitas Metode Seven Jumps dan Klasikal terhadap Pengetahuan Mahasiswa tentang Discharge Planning Postpartum - Nurhayati Nurhayati (Faletehan Health Journal, 2022)
Discharge planning postpartum is a systematic planning process from the beginning of the patient's arrival until the time he leaves the health service. Some health workers, especially midwives, sometimes do not run it optimally. It is predominantly done when the patient is about to go home by giving a re-control letter only. So it is necessary to explore the competence of discharge planning optimally and professionally. The purpose of this study was to determine the effectiveness of seven jumps and classical method on student knowledge of postpartum discharge planning. The research method used quasi experiment with pretest and posttest control group design. The total samples were 25 students as respondents; 14 students joined intervention group who got seven jumps method and 11 students joined control group who got classical one. The data collection technique used a questionnaire. The data analysis used Wilcoxon test and Mann Whitney test. The results of Wilcoxon test showed an improvement of knowledge of discharge planning postpartum by using seven jumps method in intervention group (p-value 0.001) and by using classical method in control group (p-value 0.003). The results of Mann Whitney test (p-value 0.285) showed no significant difference between the intervention group and the control group. To conclude, seven jumps and classical method are effective to improve student knowledge of discharge planning post partum. However, there is statistically no significant difference between both methods.